The philosophy of Christopher Nolan - Eberl, Jason T.; Dunn, George A., 1957- (The Philosophy of popular culture, 2017)
The Philosophy of Christopher Nolan collects sixteen essays written by philosophers and film theorists analyzing moral, metaphysical, epistemological, and political themes that characterize the films of Christopher Nolan.